PEMAKNAAN KHALAYAK TERHADAP LIRIK LAGU FOREVER NO TO DOG MEAT DAN KRITIK SOSIAL GRUP MUSIK VOX MORTIS - Farhan Rizky Muhammad; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The purpose of this research is to describe various audience receptions of “Forever No To Dog Meat” song lyrics and social criticism of Vox Mortis musical group. This research is qualitative descriptive study with interpretive paradigm and phenomenological approach. The research data was obtained by conducting indepth interviews with informants who are the members of Magelang Death Metal community. This research concludes that target audience of the song which intented to be divided into three groups of audience, which are people who run dog meat culinary business, dog meat consumers, and people who still gave beliefs about dog meat’s efficacy. Furthermore, the audience assume that the song lyrics were a form of criticism conveyed by a group of dog lovers who were furious with the practice of dog meat commercialization which involves torture and indications of criminal acts behind it. The audience tend to interpretate the topics and messages of the song lyrics differentyly based on their experiences and personal values. The audience consider that song lyrics can have a certain impact in the audience, as long as the message that contained in the song lyrics has strong relevance to the issues and problems that occur in society. The emotional involvement between the individual and the message that contained in the song lyrics are also be known as on of the influencing factors of the audiences.